(untitled) - Fry, Edward B. (New York, 2006)
This comprehensive fifth edition of a bestselling classic offers an unparalleled source of timely, practical information on all aspects of reading instruction. Ready for immediate use, it offers over 190 up-to-date lists for developing instructional materials and lesson planning. The book is organized into 15 convenient sections full of practical examples, key words, teaching ideas, and activities that can be used as is or adapted to meet students’ diverse needs. New topical areas include: ideas for non-narrative reading; word walls; graphic organizer and concept development software; new literacies, such as ’zines, Internet terms, emoticons, e-mail, and chat; as well as weekly writing prompts.
Keywords: Reading,Curriculum planning,Đọc hiểu,Kế hoạch chương trình giảng dạy